Analisis Hubungan Perceived Ease of Use dan Kualitas Layanan Terhadap Rasa Percaya Pada Alat Digital Radiografi Dalam Meningkatkan Word of Mouth Studi Pada Rumah Sakit Rujukan Covid-19 - Dimyati Ayatulloh; Ratna Wardani (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: With the times, Convention Radiography (RK) was replaced by Digital Radiography (RD) because film printing is more efficient, archiving can be done digitally, reducing the risk of losing film due to file backups, and is more environmentally friendly because it does not require chemicals. The purpose of the study was to analyze the perceived ease of use influence on the radiographer's confidence from the digital radiography tool so that word of mouth was achieved to other radiographers at the Covid-19 Referral Hospital.Methods: Design observational research with a cross-sectional approach. The population of all radiographers from 180 Covid 19 referral hospitals has used Digital Radiography. A sample of 170 respondents with cluster random sampling technique. The variables in the study were perceived ease of use, quality of service, user confidence and word of mounth. Research instruments use questionnaire sheets. The analysis used is bivariate analysis and path analysis with SPSS 23 and STATA 13.Results: Design observational research with a cross-sectional approach. The population of all radiographers from 180 Covid 19 referral hospitals has used Digital Radiography. A sample of 170 respondents with cluster random sampling technique. The variables in the study were perceived ease of use, quality of service, user confidence and word of mounth. Research instruments use questionnaire sheets. The analysis used is bivariate analysis and path analysis with SPSS 23 and STATA 13.Conclusions: The development of this technology is used as an excuse that facilitates the subscription of transportation services in fulfilling the quality of their services and makes it easier for consumers or the public to access health services. Healthcare providers mostly achieve success because they are influenced by word of mouth communication or word of mouth marketing.